Facies selectivity of benthic invertebrates in a Permian/Triassic boundary microbialite succession: Implications for the "microbialite refuge" hypothesis. Issue 5 (23rd May 2019) - Foster, William J.; Lehrmann, Daniel J.; Yu, Meiyi; Martindale, Rowan C.
Abstract: Thrombolite and stromatolite habitats are becoming increasingly recognized as important refuges for invertebrates during Phanerozoic Oceanic Anoxic Events (OAEs); it is posited that oxygenic photosynthesis by cyanobacteria in these microbialites provided a refuge from anoxic conditions (i.e., the "microbialite refuge" hypothesis). Here, we test this hypothesis by investigating the distribution of ~34, 500 benthic invertebrate fossils found in ~100 samples from a microbialite succession that developed following the latest Permian mass extinction event on the Great Bank of Guizhou (South China), representing microbial (stromatolites and thrombolites) and non‐microbial facies. The stromatolites were the least taxonomically diverse facies, and the thrombolites also recorded significantly lower diversities when compared to the non‐microbial facies. Based on the distribution and ornamentation of the bioclasts within the thrombolites and stromatolites, the bioclasts are inferred to have been transported and concentrated in the non‐microbial fabrics, that is, cavities around the microbial framework. Therefore, many of the identified metazoans from the post‐extinction microbialites are not observed to have been living within a microbial mat. Furthermore, the lifestyle of many of the taxa identified from the microbialites was not suited for, or even amenable to, life within a benthic microbial mat. The high diversity of oxygen‐dependent metazoans in the non‐microbial facies on the Great Bank of Guizhou, and inferences from geochemical records, suggests that the microbialites and benthic communities developed in oxygenated environments, which disproves that the microbes were the source of the oxygenation. Instead, we posit that microbialite successions represent a taphonomic window for exceptional preservation of the biota, similar to a Konzentrat‐Lagerstätte, which has allowed for diverse fossil assemblages to be preserved during intervals of poor preservation.